Ultrasound Guided Stellate Ganglion Block on Patient with Lung Cancer for Pain Management - Prihartono, M. Andy; Yadi, Dedi Fitri; Redjeki, Ike Sri (Perdatin Pusat, 2015)
Lung cancer is most common cancer that cause metastases. Complex regional pain syndrome (CPRS) type 1 is very severe symptoms such as pain occuring in the damaged tissue that is not caused by trauma and no nerve damage. Stellate ganglion blockade is a blockade on sympathetic nerve ganglion performed on the neck parallel to the cricoid cartilage and Chassaignac’s tubercle (C6). To determine the effectiveness of stellate ganglion block on lung cancer and complex regional pain syndrome type 1 Case report; 65 years old male with lung adenocarcinoma complained of severe pain in the lower back area of the right scapula and shoulder that radiates to the arm and fingers. For the pain, given 8mg hydromorphone (Jurnista®) 1x a day, 4x 500mg paracetamol, 10mg amitriptylin 1x and 2x 75mg pregabalin. Due to increasing pain (VAS 9), liver function and coagulopathy, the stellate ganglion blockade was performed with ultrasound guidance, pain VAS was reduced to four. Pain therapy in lung cancer accompanied with CRPS type 1 can be treated with stellate ganglion blockade in addition to pain therapy can also reduce the amount of oral medications consumed.